Inverse probability of treatment analysis of open vs endovascular repair in ruptured infrarenal aortic aneurysm – Cohort study. (August 2020) - Eilenberg, Wolf; Schwarz, Michael; Schoder, Maria; Klinger, Markus; Kinstner, Christian; Nanobachvili, Josif; Huk, Ihor; Neumayer, Christoph; Heinze, Georg; Domenig, Christoph M.
Abstract: Background: To compare open repair (OR) with EVAR for the management of ruptured infrarenal abdominal aortic aneurysms (RAAA) in a cohort study over a time period of 15 years with inverse probability of treatment weights. Material and methods: From 2000/01 through 2015/12 136 patients were treated for RAAA, 98 (72.1%) underwent OR, 38 (27.9%) were treated with EVAR. Thirty-day and long-term mortality (survival) were analyzed in this IRB-approved retrospective cohort study. Treatment modalities were compared using inverse probability of treatment weights to adjust for imbalances in demographic data and risk factors. Results: EVAR patients were older (75.11 ± 7.17 vs 69.79 ± 10.24; p = 0.001). There was no statistical difference in gender, hypertension, COPD, CAD, or diabetes. GFR was significantly higher in OR patients (71.4 ± 31.09 vs. 53.68 ± 25.73). Postoperative dialysis was required more frequently in EVAR patients: 11% vs. 2% (p = 0.099). In the OR group, adjusted cumulative survival was 70.4% (61.1, 81.1) at 30 days, 47.0% (37.1, 59.6) at one year and 38.3% (28.6, 51.3) at 5 years. In the EVAR group the corresponding numbers were 77.0% (67.7, 87.5), 67.5% (57.0, 80.0) and 41.7% (30.4, 57.4), respectively. Conclusion: There is evidence for EVAR patients exhibiting a benefit in one-year survival, while patients treated with OR may have more favorable long-term survival given they survive for at least one year. Herein we provide a statistically rigorous comparison of OR and EVAR in short and long-term outcomes with up to 15 years of follow-up. Highlights: In the light of the NICE-criteria, the first study to provide a statistically rigorous comparison of OR and EVARfor long term outcomes which is maximally adjusted for possible differences in patient characteristics. In OR patients, there is a trend towards better long-term outcome with regards to patient survival. In accordance with the NICE-criteria, EVAR patients were significantly older and hemodynamically stable.